System for Determining House Credit Recipients Based on Data of Cooperative Members Using Simple Additive Weighting (SAW) - Wiwiet Herulambang; Fardanto Setyatama; Muhammad Zulfikkih (JEECS (Journal of Electrical Engineering and Computer Sciences), 2020)
PMS Employee Cooperative is a savings and loan cooperative which aims to provide storage and loan services to employees who work at PT. Pro Manunggal Solusi and does not yet have a Decision Support System (SPK). A decision support system is needed in determining the eligibility of cooperative loans to employees. This study aims to help simplify and accelerate and minimize errors that occur in the cooperative borrower feasibility assessment process. The method used for this decision is to use the Simple Additive Weighting (SAW) method. Six criteria are used for the loan eligibility assessment process, namely criteria 1 (Loan size), criterion 2 (Loan Purpose), criterion 3 (Salary), criterion 4 (Position), criterion 5 (Age), criterion 6 (Period of service). Based on the results of the calculation, it can be concluded that each loan employee will be approved according to the ranking and is limited by the balance. If the balance is sufficient, the loan will be approved, but if the balance is less, the loan will be rejected. Of the total value of the ranking results, loans approved with a sufficient balance were Susanto (0.82) with a 12.13% chance, Sentot Sudiyantono (0.80) with a probability of 11.83%, and Siswandi (0.73) with big chance 10.80%.